THE INFLUENCE OF ELITE EDUCATION ON PERSONALITY FORMATION - L.A. Kurbanova (European International Journal of Pedagogics, 2023)
Personal elitology (or “elitological personalism”) is a component of anthropological elitology and analyzes the intellectual problems of the activities of the elite (meritocracy, aristocracy of consciousness) that fully describe the foundations of the spiritual world of a person expressing universal values. “Elitology” and “Personalism” come together here for the first time to create a general picture of the spiritual growth of a perfect person, to look into the world of lofty ideas of this person and to create an idea of his/her true essence. Thus, “elitological personalism” is the core of anthropological elitology, the central problem that fully illuminates its content. The article discusses this.